Evaluation of oral health impact profile-14 in head and neck cancer patients with oral manifestation: Evaluasi oral health impact profile-14 pada pasien kanker kepala dan leher dengan manifestasi oral - Ridho, Faiznur; Hapid, Hasan; Nur’aeny, Nanan (Makassar Dental Journal, 2024)
Oral health impact profile-14 (OHIP-14) is a method used to measure oral health quality of life (OHRQoL) after radiotherapy. This case report aims to evaluate OHIP-14 before and after head and neck cancer treatment. In case-1, a 51-year-old man complained of an unpleasant sensa-tion in the mouth, loss of taste, and dry lips after undergoing the 17th cycle of radiotherapy. Case-2, a 24-year-old man complained of dry mouth and unpleasant sensation inside the mouth especially when eating and drinking after undergoing 3rd cycle radiotherapy. Both were diagnosed with stage III tongue cancer. The patients were referred to the Department of Oral Medicine. The patients were diagnosed with oral mucositis, acute pseudomembranous candidiasis, exfoliative cheilitis and xerostomia. Patients were treated with mechanical cleaning using gauze soaked in 0.9% NaCl, gargling with 0.025% hyaluronic acid three times daily for oral mucositis, nystatin oral suspension for oral candidiasis, vaseline album and GC dry Mouth® topical commercial gel for dry lips and xerostomia. The OHIP-14 scores of both patients decreased. It was concluded that a decrease in OHIP-14 score indicates successful treatment of head and neck cancer patients with oral complications after radiotherapy.